The importance of correct labelling of types: an example in Tortricidae (Lepidoptera) and its rectification - Aarvik, Leif; Prins, Willy De (Zootaxa, 2017)
Taxonomy is the basic discipline in biology. The taxonomist defines each taxon and provides a unique name for it. Of the systematic categories, the species level is crucial. When a species is described and named, great care should be taken to ensure that all information related to the name is correct. Information on ecology, biology, distribution, etc. is linked to the name, and may be added and repeated in subsequent literature. Great confusion may arise from ambiguous descriptions and/or mislabelled figures. Therefore editors should take special care to ensure that taxonomic papers containing descriptions of new taxa receive careful refereeing and editing. Here we present a case where descriptions of new species became misleading when the labels of the type specimens were switched. If the manuscript had been more thoroughly refereed, the mistake could have been discovered and avoided.